Advancing European entrepreneurship research : entrepreneurship as a working attitude, a mode of thinking and an everyday practice - Gnan, Luca; Lundberg, Hans; Songini, Lucrezia; Pellegrini, Massimiliano M. (The Entrepreneurship SIG at European Academy of Management: new horizons with strong traditions, 2014)
The objective with the Strategic Interest Group in Entrepreneurship (SIG Entrepreneurship) of the European Academy of Management (EURAM) is to be the leading research community for engaged entrepreneurship scholars in Europe. The SIG Entrepreneurship aims at promoting research and networking interests for individuals and research groups focused on entrepreneurship and entrepreneurial styles of management. This is done by providing a wide-ranging, engaged and internationally-focused forum to discuss and develop research and practice in the field. We put a distinct focus on the key European feature - 'context matter' - why we try in all activities to promote and stimulate what 'European' might mean in any given context. It means different things in different contexts - and that is the whole point - and thereby the key strength of the European takes on the matter as we see it. This is our idea of the European perspective on entrepreneurship.The tradition of European scholars on entrepreneurship and SMEs system has been consolidated during the last three decades and an increasingly distinct European school of thought has emerged as a consequence. This development provides a solid base for the future development of the field where Europe and its entrepreneurship scholars will play an increasingly prominent role. With this concern, this book has been managed, gathering the best contributions of our annual meeting re-edited and improved. The central theme is presenting entrepreneurship understood as a working attitude, a mode of thinking, a concrete everyday practice and increasingly an identity marker for ways of being and living within liquid modernity. Entrepreneurship is nowadays a broadly endorsed and accepted signifier for forms of organizing that targets human, organizational and economic renewal and growth.